Chemical and Mineralogical Characteristics of an Organic Soil (Troposaprist) from Sg. Burong, Tg. Karang, Selangor - Jusop, Shamsuddin; Nik Wan, Nik Mokhtar; Kamal, A. J. (1985)
At bulk density of O. 97 g/cm 3and pH (top soil) of around 5 reflects that the soil has improved after undergoing an ameliorating programme and more than a decade of cultivation. But at depth, pH is still low where Al is present in large quantities. A high water table leads to the accumulation of bases, especially Ga and Na in the lower horizons. Low pH0 and high GEG is the reflection of high amounts of organic matter and mica-vemiculite-smectite mineralogy.